3D Bioprinting for Spinal Cord Injury Repair - Yuan, Tian-Yang; Zhang, Jun; Yu, Tong; Wu, Jiu-Ping; Liu, Qin-Yi (Frontiers in Bioengineering and Biotechnology, 2022)
Spinal cord injury (SCI) is considered to be one of the most challenging central nervous system injuries. The poor regeneration of nerve cells and the formation of scar tissue after injury make it difficult to recover the function of nervous system. With the development of tissue engineering, 3D bioprinting has attracted extensive attention because it can accurately print complex structures. At the same time, the technology of blending and printing cells and related cytokines has gradually matured. Through this technology, complex biological scaffolds with accurate cell localization can be manufactured. Therefore, this technology has a certain potential in the repair of the nervous system, especially the central nervous system. So far, this review focus on the progress of tissue engineering of nervous system, landmark 3D bioprinting methods and landmark 3D bioprinting applications of spinal cord in recent years.